Indeks Massa Tubuh Menurut Usia, Aktivitas Fisik, dan Pola Makan Pada Remaja SMP Negeri 13 Semarang - Andrea Putri Sekar Tunjung; Gregorius Tsiompah; Oktavina Permatasari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Nutritional status is a health condition that occurs as a result of a comparison between needs and the fulfillment of nutritional substances. There are several factors that can influence a person's nutritional status, namely suitability of needs with food intake, physical activity, increased nutritional needs due to various diseases, and other factors such as social and economic background. The nutritional status of adolescents can be described through measuring BMI/U. The prevalence of underweight in adolescents aged 13-15 years, based on research and development data from the Ministry of Health in 2013, is 11.1% (3.3% very thin and 7.8% thin) while for obese people aged 13-15 years was 10.8% (2.5% very obese and 8.3% obese). Data was obtained by interviews regarding identity, student age, weight and height measurements, exercise and physical activity habits, eating patterns and interpretation of nutritional status on Z-Score BMI according to Age. The results of this study showed that 59.5% of students had good nutritional status, 15.7% of students had overweight nutritional status, 13% of students have poor nutritional status, 10.3% of students have poor nutritional status, 1.6% students have obesity nutritional status.